New frontiers in circulating tumor cell analysis: A reference guide for biomolecular profiling toward translational clinical use. Issue 11 (29th October 2013) - Becker, Therese M.; Caixeiro, Nicole J.; Lim, Stephanie H.; Tognela, Annette; Kienzle, Norbert; Scott, Kieran F.; Spring, Kevin J.; de, Paul
<x xml:space="preserve">Abstract</x> Circulating tumor cells (CTCs) are now routinely isolated from blood, and measurement of CTC concentrations appears to correlate well with survival in patients with cancer. Interrogation of the molecular profile of CTCs for expression of protein biomarkers, genetic variants and gene expression provides opportunities to use this information to guide personalized treatment, monitor therapy and detect emerging resistance. However, successful application of profiling techniques requires analyses that deliver a reliable and clinically relevant representation of a patient's cancer as it changes with time. Here, we comprehensively review the current knowledge of therapeutically relevant biomarkers in isolated CTCs obtained by fluorescence imaging and genomic profiling approaches. The reviewed data support the notion that molecular profiling of CTCs will provide a reliable representation or surrogate index of tumor burden. Large‐scale translational trials, many currently in progress, will provide critical data to progress CTC analysis toward wider clinical use in personalized treatment.